Hello Talk: An Alternative Media for Improving Writing Skills for Higher Education - Febriani, Suci Ramadhanti; Widayanti, Rizka; Saputra, Hendri Yahya; Safutri, Janniarni Toha; Bedra, Kddour Guettaoui (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
Productive language skills are an indicator of student success in using foreign languages. The lack of media allows students to interact with native speakers. It encourages researchers to analyze holistically how to use the HelloTalk application as an alternative media for increasing writing skills. This study used a qualitative descriptive research design—data collection techniques through observation, interview, and documentation. The data collection tools are based on pre-test and post-test scores, observation sheets, and a list of questions from interviews. The analysis technique used is Milles Huberman's theory. The results show that the HelloTalk application can provide opportunities for students to increase creativity and critical thinking. The ability students' showed an increase in score to 75.3. This result is indicated by using chat themes in broader writing skills and interaction with native speakers to explore information on the language being learned. In addition, the process of correcting writing errors can be corrected immediately. The findings of this research indicate that using the HelloTalk application increases the intensity of Arabic writing skills. This study recommends further research to test the effectiveness of the HelloTalk application against other foreign language skills with more varied research methods.